Belle Épine - Zlotowski, Rebecca; Lechaptois, Georges; Seydoux, Léa; Demoustier, Anaïs; Schlenker, Agathe
The good girl attracted to the guy racing motorcycles is a trope of adolescent rebellion going back to "The Wild One" (1953). Debut director/co-writer Rebecca Zlotowski delves unusually deep and sensitively into what drives one French 17 year old to hop on back. The family of Prudence Friedmann (Léa Seydoux) is reeling from the death of the mother, making Prudence feel abandoned and alone, despite relatives who take her into their observant Jewish home. She isn't just led astray by the bad girl at school. She chooses the dark thrills and excitement of a late-night motorcycle hangout to mask her grief by experimenting with sex and drugs until she can finally, and touchingly, face her mother's memory. [film-forward.com]